ChemInform Abstract: Synthesis of Axially Chiral Biaryl Compounds by Asymmetric Catalytic Reactions with Transition Metals. Issue 18 (April 2016) - Loxq, Pauline; Manoury, Eric; Poli, Rinaldo; Deydier, Eric; Labande, Agnes
Abstract: Review: 297 refs.